Development of a Novel Pomegranate Polysaccharide Nanoemulsion Formulation with Anti-Inflammatory, Antioxidant, and Antitumor Properties - Hoseny, Samah S.; Soliman, Amel M.; Fahmy, Sohair R.; Sadek, Shimaa A. (Current Drug Delivery, 2023)
Background: Colorectal cancer is one of the most serious gastrointestinal cancers in Africa and its prevention is a pronounced challenge in contemporary medicine worldwide. Objective: The present study aimed to develop nanoemulsion drug delivery system using pomegranate polysaccharides (PGPs) as an alternative cancer remedy, and then the evaluated its biological activities. Methods: The PGPs yield and chemical composition were evaluated, and then a PGPs nanoemulsion (PGPs-NE) was prepared using the self-emulsification technique with an oil phase. The physicochemical characterization of PGPs-NE was then analyzed. The in vitro antioxidant, anti-inflammatory activities, and antitumor potency of PGPs and PGPs-NE were also evaluated. Results: The PGPs yield was 10%. The total sugar and protein content of PGPs was 44.66 mg/dl and 19.83μg/ml, respectively. PGPs were mainly composed of five monosaccharides including fructose, glucose, galactose, rhamnose, and arabinose. Concerning physiochemical characterization, the formulated PGPs-NE had three optical absorption bands at 202, 204, and 207nm and a transmittance of 80%. Its average hydrodynamic particle size was 9.5nm, with a PDI of less than 0.2 and a negative zeta potential (-30.6 mV). The spherical shape of PGPs-NE was confirmed by a transmission electron microscope study, with an average size of less than 50 nm. Additionally, the method used to prepare the PGPs-NE formulation provided high entrapment efficiency (92.82%). The current study disclosed that PGPs-NE exhibited strong antioxidant, anti-inflammatory, and antitumor agent potency compared to that of free PGPs. Conclusion: These promising current findings provide evidence for the possible efficacy of novel PGPs-NE as an alternative treatment for CRC.
Keywords: pomegranate polysaccharides